A four-phase framework for Lean implementation in small and medium enterprises - Minh Nguyen Dat; Kien Duon Trung (Zielona Góra: Faculty of Economics and Management Press)
Although Lean has been known and applied in both theoretical and practical on around the world for many years, a deeper understanding of Lean tools, principles implementation, and a roadmap to successfully apply is needed. In the context of Small and medium enterprises (SME), it is very difficult for local enterprises to apply synchronization Lean tools, techniques, and principles because of limited resources in manpower, technology, and management capability.
Keywords: LEAN application; LEAN manufacturing; LEAN outcome; small and medium enterprises (SME); SME; aplikacja LEAN; narzędzia LEAN; LEAN zastosowanie; małe i średnie przedsiębiorstwa